2021
DOI: 10.1007/s11356-021-15627-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutual impacts and interactions of antibiotic resistance genes, microcystin synthetase genes, graphene oxide, and Microcystis aeruginosa in synthetic wastewater

Abstract: The physiological impacts and interactions of ARGs abundance, microcystin synthetase genes expression, GO, and M. aeruginosa in synthetic wastewater were investigated. The results demonstrated that the absolute abundance of sul1, sul2, tetW, and tetM in synthetic wastewater dramatically increased to 365.2%, 427.1%, 375.2%, and 231.7%, respectively, when the GO concentration was 0.01 mg/L. Even more interesting is that the sum gene copy numbers of mcyA-J also increased to 243.2%. The appearance of GO made the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 64 publications
(65 reference statements)
1
14
0
Order By: Relevance
“…This screening revealed eight additional papers. Thus, a total of 39 papers are included in this review, most of which include multifactorial experiments, such as different contaminants, strains, or additional experimental treatments other than contaminants. …”
Section: Literature Review Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…This screening revealed eight additional papers. Thus, a total of 39 papers are included in this review, most of which include multifactorial experiments, such as different contaminants, strains, or additional experimental treatments other than contaminants. …”
Section: Literature Review Methodologymentioning
confidence: 99%
“…This review revealed numerous studies showing that various chemicals often induce hormesis in HAB-forming and toxin-producing cyanobacteria (blue-green algae), in particular, in different strains of Microcystis wesenbergii , and M . aeruginosa . ,, ,,, , , However, hormetic responses were also revealed in the neurotoxin-producing Anabaena flos-aquae and the bloom-forming haptophyte Prymnesium parvum , which produces the phycotoxin prymnesi . Such hormetic responses were further identified in Synechocystis sp., which may also contribute to bloom formation .…”
Section: Occurrence Of Hormesis In Harmful Algaementioning
confidence: 97%
See 1 more Smart Citation
“…A further survey of the literature for the purpose of this study revealed ample evidence suggestive of hormesis for numerous aquatic organisms and various pollutants and emerging contaminants in dozens of publications, of which only a few selected examples are cited here (older examples can also be traced in the therein references). These examples include a plethora of species, such as of algae (microphytes) [38][39][40][41][42][43][44][45][46][47][48][49] , aquatic flowering plants [50] , organism-attached biofilms [51] , crustaceans [52][53][54][55][56][57] , cyanobacteria [49,[58][59][60][61] , fishes [62][63][64][65][66][67][68][69] , macrophytes [70][71][72][73][74][75] , marine polychaete [76] , mollusks (e.g., clams and mussels) [77,78] , periphyton [79] , phytoplankton [80] , sea anemones [81,82] , and snails [83] . Responses suggestive of hormesis were found for molecular (molecules...…”
mentioning
confidence: 99%
“…Responses suggestive of hormesis were found for molecular (molecules involved in oxidative stress), cellular (e.g., growth and density), and whole-organism (e.g., growth and body mass) endpoints, as well as endpoints suggesting potential sub-NOAEL effects on organismic interactions, such as via altered feeding activity [83] . Such responses were induced by chemicals such as antibiotics/antifungals [38,39,42,45,50,51,67,70,71,75] , steroid hormones [41,83] , and other human drugs [63,69] , bisphenol A and its substitutes [66] , chemical leached from disposed light sticks [55] , electroplating processemitted particulate matter [40] , effluents from textile-dyeing wastewater treatment plants [46] , fullerene crystals (nC 60 ) [57] , metals and ionic liquids [62,77,81,82] , micro/nanoplastics and their leachates [43,44,47,53,60,64,80,84] , engineered nanomaterials [58,59,61,65] , pesticides [48,49,52,56,[72][73][74]79,84] , phthalic acid esters ...…”
mentioning
confidence: 99%